1988
DOI: 10.1080/1355800880250405
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Video and Artificial Intelligence: A Convenient Marriage

Abstract: This paper describes the theoretical framework of a research project aimed at exploring the new potentialities for instructional systems offered by videodisc technology and artificial intelligence methodologies and techniques. In the context of this project, 'Earth', a prototype of ITS, is being developed, which embodies the ideas presented. In an instructional system, interaction can be characterized by three properties: adaptivity, reactivity and flexibility. The existing interactive systems are adaptive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although it may seem that such massive investment may not be necessary for developing many other learning environments, there are several general design principles that Kilb et al (2001) used, which are relevant for effective planning of most interactive learning environments, such as analyzing the needs of both instructors and learners, identifying different types of learners and providing them with appropriate interactive content, and letting the users modify the system according to their needs. Midoro et al (1988) characterized interactivity by three properties: adaptivity, reactivity, and flexibility, and suggested Artificial Intelligence (AI) techniques for assisting learners in interactive video learning environments. It is essential to evaluate the effectiveness of interactive media (Laurillard & Taylor, 1994), and previous studies such as Hannafin and Colamaio (1987), demonstrated the value of interactive video as a specific media for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Although it may seem that such massive investment may not be necessary for developing many other learning environments, there are several general design principles that Kilb et al (2001) used, which are relevant for effective planning of most interactive learning environments, such as analyzing the needs of both instructors and learners, identifying different types of learners and providing them with appropriate interactive content, and letting the users modify the system according to their needs. Midoro et al (1988) characterized interactivity by three properties: adaptivity, reactivity, and flexibility, and suggested Artificial Intelligence (AI) techniques for assisting learners in interactive video learning environments. It is essential to evaluate the effectiveness of interactive media (Laurillard & Taylor, 1994), and previous studies such as Hannafin and Colamaio (1987), demonstrated the value of interactive video as a specific media for learning.…”
Section: Introductionmentioning
confidence: 99%
“…The same group of authors proposes an example of such flexible/adaptive system -"Earth", where plate tectonics can be approached from historical point of view, or the user can choose to learn the basic concepts of this theory, or concentrate on learning tectonics of a particular area. This approach has much promises for the future development of intelligent CAI, and at the same time points out the need for more research in the area of basic aspects of learning and teaching [Midoro et al, 1988 andBacker, 1988].…”
Section: Tutoring and Tutorialsmentioning
confidence: 99%